Participatory problems identification in goat rearing through rank based quotient method in Rajasthan, India - MEENA, M S; SINGH, S K; MEENA, H N; VERMA, G S; CHOUDHARY, ANURADHA (The Indian Journal of Animal Sciences, 2022)
Goat farming is a suitable option for revenue generation for small-scale farmers and tribal people as it requires meager investment. Goats can efficiently survive and sustain on sparse vegetation and extreme climatic conditions. Hence, a study was undertaken in the tribaldominated Banswara district of Rajasthan state to identify problems perceived by youths in goat rearing. A total of 73 tribal youth responded to the study. RBQ technique was employed to identify the problems in goat farming. Predators attack was identified as a major problem (87.67%), followed by lack of funding and unavailability of improved goat breeds (87.24%). So, this study recommended that to prevent goats from predators, proper housing is necessary. So, KVK should maintain follow-ups with participants and provide financial help to initiate venture after skill development. Therefore, youths’ migration from rural to urban area could be optimized intribal areas. In addition to the ARYA project, the integration of various government schemes would benefit scaling up this profitable venture for tribal youths.